Degradation of 1,4-dichlorobenzene by Alcaligenes sp. strain A175. - Schraa, G (1986)
An organism, identified as an Alcaligenes sp., was isolated from an enrichment culture in which 1,4-dichlorobenzene served as the sole carbon and energy source. During growth with 1,4-dichlorobenzene in pure culture, stoichiometric amounts of chloride were released. Growth experiments and oxygen uptake rates with other chlorinated aromatic compounds revealed a high degree of specificity of the initial dioxygenase. cis-1,2-Dihydroxycyclohexa-3,5-diene oxidoreductase and 1,2-pyrocatechase, but not 2,3-pyrocatechase, were found in cell extracts, while 3,6-dichlorocatechol and (2,5-dichloro)muconic acid could be detected as intermediates during degradation of 1,4-dichlorobenzene. It is proposed that dioxygenases are involved in the initial steps of 1,4-dichlorobenzene degradation, while ring opening proceeds via ortho cleavage.